Prevalence and Persistence of Misconceptions in Tree Thinking - Tyler A. Kummer (American Society for Microbiology, 2016)
Darwin described evolution as “descent with modification.” Descent, however, is not an explicit focus of most evolution instruction and often leaves deeply held misconceptions to dominate student understanding of common ancestry and species relatedness. Evolutionary trees are ways of visually depicting descent by illustrating the relationships between species and groups of species. The ability to properly interpret and use evolutionary trees has become known as “tree thinking.” We used a 20-question assessment to measure misconceptions in tree thinking and compare the proportion of students who hold these misconceptions in an introductory biology course with students in two higher-level courses including a senior level biology course. We found that misconceptions related to reading the graphic (reading the tips and node counting) were variably influenced across time with reading the tips decreasing and node counting increasing in prevalence. On the other hand, misconceptions related to the fundamental underpinnings of evolutionary theory (ladder thinking and similarity equals relatedness) proved resistant to change during a typical undergraduate study of biology. A possible new misconception relating to the length of the branches in an evolutionary tree is described. Understanding the prevalence and persistence of misconceptions informs educators as to which misconceptions should be targeted in their courses.